Design Criteria for Visual Cues Used in Disruptive Learning Interventions Within Sustainability Education - Holland, Charlotte; Salomão Filho, Alfredo; Tillmanns, Tanja (Discourse and Communication for Sustainable Education, 2017)
This paper presents the design criteria for Visual Cues – visual stimuli that are used in combination with other pedagogical processes and tools in Disruptive Learning interventions in sustainability education – to disrupt learners’ existing frames of mind and help re-orient learners’ mind-sets towards sustainability. The theory of Disruptive Learning rests on the premise that if learners’ frames of mind or frames of reference can be disrupted (in other words, challenged), then learners’ mind-sets can be re-oriented towards sustainability, and indeed learners can be motivated to engage in change agency for sustainability. The use of Visual Cues thus unsettle or challenge learners’ mind-sets, and in doing so, set them on the pathway towards re-orientation in becoming more sustainability oriented, and/or in motivating engagement in sustainability change agency. The findings form part of a broader research study on ESD conducted in a higher education institution in Ireland within an undergraduate degree of teacher education. Kathy Charmaz’ Constructivist Grounded Theory approach guided the entire study, resulting in the articulation of the theory of, and processes within, Disruptive Learning. This paper presents design criteria for Visual Cues that were articulated through a thematic analysis approach from data emerging from reflective diaries, follow-up interviews, audio recordings and observational notes. The findings from this study in respect of design criteria state that Visual Cues must disrupt rather than disturb; must represent (have impressions of) real life contexts, scenarios, practices or events; must provoke controversy; must contain a visual stimulation; and can have a critical question.<br
Keywords: Disruptive Learning; Visual Cue; pedagogy; sustainability education; higher education